3D-Printed Template-Guided 125I Seed Brachytherapy: A Salvage Approach for Locoregional Refractory Recurrence of Papillary Thyroid Cancer. Issue 6 (4th November 2021) - Gao, Zhen; Zhang, Hongtao; Zhang, Lijuan; Yu, Huimin; Di, Xuemin; Wang, Zeyang; Liu, Zezhou; Sui, Aixia; Wang, Juan; Shi, Gaofeng
Abstract : Background: Papillary thyroid carcinoma (PTC) is typically treated with surgical resection, even in recurrent cases. However, some cases of recurrent PTC are refractory to the conventionally used locoregional radiotherapy and resection methods. 125 I seed permanent brachytherapy has emerged as a promising alternative for such PTCs, but no effective brachytherapy protocol has been reported for tumors with a huge volume, liquefaction, necrosis, and skin invasion. Case Presentation: A 47-year-old man presented with recurrence 8 years after 2 thyroidectomy procedures for PTC and recurrent PTC. The tumor measured 6 × 7 × 8 cm 3 and exhibited liquefaction, necrosis, and skin invasion. The patient was treated at our hospital from December 2017 to November 2018. He received one round of 125 I seed temporary brachytherapy and 4 rounds of 125 I seed permanent implantation. The activity of the seeds was 0.3–3.0 mCi, and the total dose delivered to the tumor was 145 Gy. The recurrent tumor was successfully removed by 125 I seed brachytherapy guided with a 3D-printed template and ultrasound and CT scanning. The refractory tumor healed uneventfully after 125 I seed brachytherapy without recurrence over the 25-month follow-up. Conclusions: To the best of our knowledge, this is the first reported case of a large thyroid carcinoma that was effectively treated by 3D-printed template-guided 125 I seed brachytherapy.